Prognostic Relationship Between Human Papillomavirus Status and Overall Survival in Patients with Tongue Cancer - Chayanit Kritpracha; Peesit Leelasawatsuk; Virat Kirtsreesakul; Pasawat Supanimitjaroenporn; Jarukit Tantipisit; Manupol Tangthongkum (Viruses)
An increasing number of patients are being diagnosed with tongue cancer despite lacking traditional risk factors such as tobacco, alcohol, or betel nut use. The potential role of human papillomavirus (HPV) in these cases has drawn attention, although its prognostic significance remains unclear. This retrospective cohort study, conducted in Southern Thailand, aimed to investigate the association between HPV status and overall survival in tongue cancer. Medical records of 186 patients treated between 2012 and 2021 were reviewed. HPV status was determined, and patients were categorized into HPV-negative, HPV-positive with other risk factors, and HPV-positive without known behavioral risk factors. Survival outcomes were compared using the log-rank test, and independent prognostic factors were analyzed using multivariable Cox regression. The overall prevalence of HPV infection was 9.6%, predominantly HPV16, HPV33, and HPV18. Although no significant differences were observed in 3-year overall survival, disease-specific survival, or recurrence-free survival among the groups, multivariable analysis revealed that HPV-positive patients without known behavioral risk factors (tobacco, alcohol, or betel nut use) had poorer overall survival (hazard ratio 3.54, p = 0.045). The observed associations warrant further research into the prognostic role of HPV in tongue cancer among non-smoking, non-drinking populations.